RANCANG BANGUN APLIKASI PENGARSIPAN DOKUMEN DALAM PENGELOLAAN DAN PENCARIAN PADA KANTOR PELAYANAN PAJAK PRATAMA PRABUMULIH - ALDINO PUTRA BUANA (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2023)
This research aims to design and develop a document archiving application that can assist tax officials in managing and retrieving document archives at the Pratama Tax Service Office in Prabumulih. This application is designed to streamline the document archiving process for tax officials by providing features such as input for incoming archives, outgoing archives, as well as reports on incoming and outgoing archives. Additionally, this application also ensures data security through the implementation of security protocols and data encryption. The research employs the waterfall method for designing and constructing this application, encompassing stages of requirement analysis, design, coding, and testing. The outcomes of this research are expected to enable this application to assist tax officials in effectively and efficiently managing document archives. Furthermore, it is anticipated that this application will help alleviate difficulties and inconveniences in financial reporting processes and enhance the quality of document archiving reports at the Pratama Tax Service Office in Prabumulih. Keywords: Application, Archiving, Archive Reporting.